Firm's innovation activities across ASEAN countries: Examining the impacts of management experience, management practices and the moderating role of female CEOs - Bich Ngoc Do; Van Dung Nguyen; Minh Thi Hong Le; Hai-Ninh Do; Thi Truc Ly Pham (Cogent Business & Management, 2023)
This study investigates the roles of management experience and management practices towards innovation activities across ASEAN nations. Notably, the moderating role of the female CEOs in the management experience management practices-innovation relationship is also examined. The data came from the World Bank's Enterprise Survey, consisting of 180,000 enterprises worldwide. This study extracted data from seven economies in ASEAN (Vietnam, Thailand, Indonesia, Philippines, Malaysia, Laos, and Cambodia). To deal with the hierarchical/multilevel structure of the study's data set, the study uses the multilevel mixed-effects ordered logit model. The findings reveal that both management practices and management experience have positive impacts on innovation activities, particularly product innovation. Furthermore, this paper highlights the positive moderating role of female CEOs in the management experience management practices-innovation relationship.
Keywords: 650; ASEAN countries; female CEOs; innovation; management experience; management practices